Indonesian Generation Z's Intention to Visit South Korea: The Mediating Role of Tourist Attitude on Travel Motivation and Celebrity Endorser Credibility - Gusti Ayu Citra Arya Sucisanjiwani; Putu Gde Arie Yudhistira (Universitas Airlangga, 2023)
Objective: This study examined the effect of travel motivation and celebrity endorser credibility in influencing the intention of the Indonesian Generation Z to visit South Korea, with involved a mediating role of tourist attitude, which refers to the Korean Wave Phenomenon. Design/Methods/Approach: This study was done by quantitative approach with Partial Least Square Structural Equation Modeling (PLS-SEM) analysis procedure using SmartPLS 4. The data collection technique was purposive sampling, aimed at the Indonesian Generation Z as the target respondent. There were 385 data collected using the online questionnaires. Findings: The results show that travel motivation and celebrity endorser credibility positively and significantly affect the visit intention to South Korea. Tourist attitude also mediates the relationship between travel motivation and celebrity endorser credibility in affecting the visit intention to South Korea. Originality: The existing literature discovered the direct effect of travel motivation and celebrity endorser credibility on visit intention in the tourism industry. This study contributes to the existing literature by involving tourist attitude as a mediation variable in the relationship between tourist motivation and celebrity endorser credibility in affecting visit intention to South Korea. Practical/Policy implication: This study contributes to proposing recommendations for a more effective marketing and promotion strategy for tourism products in South Korea by looking at trends in tourist preferences and involving the role of celebrities as an endorser. Research also contributes to developing literature on marketing and promoting tourism products and tourist behavior literature.